2015
DOI: 10.11604/pamj.2015.22.19.6131
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness and knowledge of the National Health Insurance in South Africa

Abstract: IntroductionIndividuals residing in Limpopo, KwaZulu-Natal and the Eastern Cape provinces who had access to public health services were surveyed to determine public knowledge and awareness of the new National Health Insurance (NHI).MethodsA descriptive cross-sectional study was conducted and a total of 748 adult respondents were sampled using a two-stage systematic sampling design. Data were collected using mobile phone assisted personal interviews.ResultsThe study found that 80.3% of the respondents were awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 9 publications
2
25
5
Order By: Relevance
“…The finding that majority of the participants of the present study were not aware of the NHI was unanticipated, because that the NHI policy process commenced in 2011 and this study was conducted 6 years later. The finding that the awareness levels of the NHI were low in the present study was also inconsistent with a similar paper by by Setswe, et al found a much higher proportion, of 80.3%, of their participants were aware of the NHI 18 . This awareness percentage is virtually the inverse of what the present study found.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding that majority of the participants of the present study were not aware of the NHI was unanticipated, because that the NHI policy process commenced in 2011 and this study was conducted 6 years later. The finding that the awareness levels of the NHI were low in the present study was also inconsistent with a similar paper by by Setswe, et al found a much higher proportion, of 80.3%, of their participants were aware of the NHI 18 . This awareness percentage is virtually the inverse of what the present study found.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though awareness on the NHI was high in the study by Setswe et al, the majority of participants had limited understanding of important concepts of health insurance. 18 The difference in the awareness levels can be attributed to the difference in the sample population involved when compared to the present study. This research focused on patients only and was conducted in a central hospital department, which is situated in an urban area only, which is not a NHI pilot site.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The finding of this research showed that the range of age was 20-59 years and majority of them were female. 3 Another study was conducted among health professionals showed that majority of them were female and majority were nurses. 11 Our finding showed that nearly half (42.03%) of the students know the meaning of free health services.…”
Section: Discussionmentioning
confidence: 99%
“…2 Free health service program provides essential health care services free of charge to all users at Primary Health Care Centers, Health Posts. 3 Similarly, outpatient, inpatient, emergency services and been regarded as one of the responsibilities of the state. The constitutional provision has set the platform for commencement of free health service program in Nepal.…”
Section: Introductionmentioning
confidence: 99%